Baltic Smart Asset Management – data driven predictive maintenance methods for future. Issue 1 (October 2020) - Hogland, William; Katrantsiotis, Christos; Asim Ibrahim, Muhammad
Abstract: This Interreg project Baltic Smart Asset Management focuses on District Heating (DH) studies in the three Baltic countries Lithuania, Poland and Sweden. Some part of the grids in the member countries start to be old and safe, secure and affordable energy supply most be delivered and reduction of CO2 emission is obvious though boilers are fed by gas, oil, coals and solid wasted and renewable energy sources must be used instead. The paper gives some basic information about district heating system and how the countries through a cross-border strategy will create awareness of preventive data driven maintenance methods energy companies based on the educational purpose to decrease harmful emissions to environment. As technological methods has improved greatly in recent years these should be given more consideration as a possible treatment option of DH instead of chemicals which can have Environmental impact in the form of the influence of metals and degradation of habitat, species etc. Involvement of associated partners and stakeholder in the work is of high importance in the project.